NF-κB regulation: The nuclear response - Mc Manus, Ross; Gray, Steven; Kelleher, Dermot (My University, 2009)
Nuclear factor ?B (NF-?B) is an inducible transcription factor that tightly regulates the expression of a large cohort of genes. As a key component of the cellular machinery NF-?B is involved in a wide range of biological processes including innate and adaptive immunity, inflammation, cellular stress responses, cell adhesion, apoptosis and proliferation. Appropriate regulation of NF-?B is critical for the proper function and survival of the cell. Aberrant NF-?B activity has now been implicated in the pathogenesis of several diseases ranging from inflammatory bowel disease to autoimmune conditions such as rheumatoid arthritis. Systems governing NF-?B activity are complex and there is an increased understanding of the importance of nuclear events in regulating NF-?B's activities as a transcription factor. A number of novel nuclear regulators of NF-?B such asI?B-? and PDZ and LIM domain 2 (PDLIM2) have now been identified, adding another layer to the mechanics of NF-?B regulation. Further insight into the functions of these molecules raises the prospect for better understanding and rational design of therapeutics for several important diseases.
PUBLISHED
Keywords: Oncology; Immunology; NF-kappa B; Nuclear Regulation; Genes & Society; Immunology, Inflammation & Infection; International Integration